Hubungan Kepemimpinan Kepala Sekolah dengan Etos Kerja Guru di Sekolah Menengah Kejuruan Negeri Se Kecamatan Guguak - Rahmi Putri; Nellitawati; Jasrial; Tia Ayu Ningrum (Deduksi: Jurnal Dedikasi Edukasi, 2023)
This research emerged as a response to the observed non-optimality in Teacher Work Ethic. The main objective of the research is to evaluate the leadership of school principals in SMK N in Guguak District, identify the level of teacher work ethic in SMK N, and assess the significance of the relationship between principal leadership and teacher work ethic at the sub-district level. This research uses a correlational approach to investigate the relationship between variables. The population studied involved 146 teachers, with 64 of them selected as samples using proportional stratified random sampling techniques based on the Cochran formula. The instrument used is a questionnaire with a Likert scale which has been tested for validity and reliability. The main findings include: 1) The leadership of school principals at SMK N in Guguak District was assessed as quite good with a score of 3.48. 2) The work ethic of teachers at SMK N in Guguak District received a high assessment with a score of 3.95. 3) There is a significant relationship between principal leadership and teacher work ethic in N Vocational Schools in Guguak District at a significance level of 5%, indicated by a correlation coefficient of 0.759, and a correlation significance test of 9.1890.